Abordări conceptuale ale familiilor cu copii în situații de risc în societatea contemporană [Articol] - Coroban, Cristina (CEP USM, 2025)
In contemporary society, the family of children at risk is a major concern for researchers, practitioners and decision-makers in the social field. These families face various challenges such as poverty, domestic violence, mental or physical health problems, lack of access to quality education and others. Conceptual approaches understand these situations as complex and multidimensional, requiring tailored and innovative interventions to support families in overcoming difficulties. The article will explore new perspectives and innovative solutions to increase the well-being of families with children at risk, reflecting current trends in research and social practice.
CONCEPTUAL APPROACHES TO FAMILIES WITH CHILDREN IN SITUATIONS OF RISK INCONTEMPORARY SOCIETY
Keywords: children at risk; families with children at risk; poverty; social risk; copii în situații de risc; familii cu copii în situații de risc; sărăcie; risc social